Layered double hydroxide/poly(vinylpyrrolidone) coated solid phase microextraction Arrow for the determination of volatile organic compounds in water. Issue 16 (24th June 2020) - Li, Xinpei; Lan, Hangzhen; Hartonen, Kari; Jussila, Matti; Wang, Xinghua; Riekkola, Marja‐Liisa
Abstract: Today, wide variety of adsorbents have been developed for sample pretreatment to concentrate and separate harmful substances. However, only a few solid phase microextraction Arrow adsorbents are commercially available. In this study, we developed a new solid phase microextraction Arrow coating, in which nanosheets layered double hydroxides and poly(vinylpyrrolidone) were utilized as the extraction phase and poly(vinyl chloride) as the adhesive. This new coating entailed higher extraction capacity for several volatile organic compounds (allyl methyl sulfide, methyl propyl sulfide, 3‐pentanone, 2‐butanone, and methyl isobutyl ketone) compared to the commercial Carboxen 1000/polydimethylsiloxane coating. Fabrication parameters for the coating were optimized and extraction and desorption conditions were investigated. The validation of the new solid phase microextraction Arrow coating was accomplished using water sample spiked with volatile organic compounds. Under the optimal conditions, the limits of quantification for the five volatile organic compounds by the new solid phase microextraction Arrow coating and developed gas chromatography with mass spectrometry method were in the range of 0.2‐4.6 ng/mL. The proposed method was briefly applied for enrichment of volatile organic compounds in sludge.